Building capacity for medical education research in family medicine: the Program for Innovation in Medical Education (PIME) - Archibald, Douglas; Hogg, William; Lemelin, Jacques; Dahrouge, Simone; St. Jean, Mireille; Boucher, François (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Despite the apparent benefits to teaching, many faculty members are reluctant to participate in medical education research (MER) for a variety of reasons. In addition to the further demand on their time, physicians often lack the confidence to initiate MER projects and require more support in the form of funding, structure and guidance. These obstacles have contributed to a decline in physician participation in MER as well as to a perceived decay in its quality. As a countermeasure to encourage physicians to undertake research, the Department of Family Medicine at the University of Ottawa implemented a programme in which physicians receive the funding, coaching and support staff necessary to complete a 2-year research project. The programme is intended primarily for first-time researchers and is meant to serve as a gateway to a research career funded by external grants. Since its inception in 2010, the Program for Innovation in Medical Education (PIME) has supported 16 new clinician investigators across 14 projects. Methods We performed a programme evaluation 3 years after the programme launched to assess its utility to participants. This evaluation employed semi-structured interviews with physicians who performed a research project within the programme. Results Programme participants stated that their confidence in conducting research had improved and that they felt well supported throughout their project. They appreciated the collaborative nature of the programme and remarked that it had improved their willingness to solicit the expertise of others. Finally, the programme allowed participants to develop in the scholarly role expected by family physicians in Canada. Conclusion The PIME may serve as a helpful model for institutions seeking to engage faculty physicians in Medical Education Research and to thereby enhance the teaching received by their medical learners.